Genetic characterization and pathological diversity of Colletotrichum falcatum went associated with red rot disease of sugarcane in Bangladesh - Hossain, Md Imam (2022)
Red rot disease caused by Colletotrichum falcatum is the most destructive disease of sugarcane (Saccharum officinarum L.) in Bangladesh and worldwide. This disease causes major financial losses to the sugarcane growers as there is no effective method to control the disease in the field. Limited information is found on the characterization, virulence pattern and genetic variation of C. falcatum, associated with red rot disease in Bangladesh. Because of this, the objectives of this study were to characterize the C. falcatum isolates of sugarcane collected from different regions in Bangladesh based on morphological and molecular characteristics and to identify the virulence patterns based on the disease reaction in differential varieties, as well as to determine the genetic diversity of C. falcatum in Bangladesh using inter-simple sequence repeat (ISSR). From August 2018 to February 2019, a total of 41 C. falcatum isolates were obtained from sugarcane diseased samples collected from four regions in Bangladesh including Rajshahi, Rangpur, Khulna and Dhaka. The experiments were carried out at Bangladesh Sugarcrop Reserch Institute Pathology Laboratory and research farm using completely randomizd design (CRD) and randomized completely block design (RCBD) respectively. The molecular identification, genetic diversity and pathogenicity studies were carried out at the Bacteriology Laboratory, University Putra Malaysia. During the field survey, all sampling areas were infected by the red rot disease, and revealed that field disease incidence ranged from 3–25% in the study areas. All the isolates were characterized and identified based on morphological and molecular characteristics. The C. falcatum isolates showed diversity in morphological traits. Colony morphology varied from dark grey, whitish-grey, grey, and greyish-white colour, with flat, less fluffy, and raised fluffy mycelial topography, and the colonies had produced appressoria, seate and falcate shape, aseptate, and hyaline colour conidia.The four genes of the 41 isolates namely internal transcribed spacer (ITS-rDNA), β-tubulin, Actin, and glaceraldehydes -3 phosphate dehydrogenase (GAPDH) sequences showed a 99–100% similarity index to the conserved gene sequences in the GenBank database. The phylogenetic analysis of the four genes revealed that C. falcatum isolates from Bangladesh were clustered in the same clade, and had no geographical distinctions. The four gene sequences also revealed that C. falcatum isolates from Bangladesh differed from other countries' isolates by nucleotide substitution at several loci positions. ISSR markers determined the low genetic diversity of the C. falcatum isolates in Bangladesh. Amongst the four populations of C. falcatum, population I (Rajshahi) had the highest genetic diversity level. While population II (Rangpur) had the lowest genetic diversity level. The cluster analysis divided the 41 isolates into four major clusters and each cluster was further divided into two sub-clusters. The clustering results revealed that C. falcatum isolates collected from the same location belong to the same sub-cluster, and a few of them belong to the other sub-clusters, indicating that the clusters were partially correlated to geographical regions and have a gene flow effect among the isolates. The virulence levels of the 41 C. falcatum isolates corresponding to disease reaction on the host plant were studied and were categorized into three main groups viz. virulent, moderately virulent, and least virulent. The seven sugarcane differential hosts were classified as resistant, moderately resistant, and susceptible. The sugarcane cultivars viz. Isd 18 and I-291-87 showed the highest level of susceptibility. While the cultivars Isd 39 and BSRI Akh45 showed the highest level of resistance. Finding revel that C. falcatum isolates carried PKS1, HXT1, and Pel2 genes. The gene sequence analysis of the virulent, moderately virulent, and least virulent isolates revealed that the nucleotide substitution and deletion occurred at several loci. To the best of our knowledge, this is the first findings on the characterization, genetic diversity and virulence pattern of C. falcatum in Bangladesh. The results from this study could serve as a framework for establishing red rot disease control program in Bangladesh. Furthermore, this information is very crucial in developing red rot disease-resistant varieties for effective disease management strategies.